STUDI KOMPARATIF HASIL BELAJAR MAHASISWA YANG BEKERJA DAN TIDAK BEKERJA PROGRAM STUDI PENDIDIKAN PANCASILA DAN KEWARGANEGARAAN FAKULTAS KEGURUAN DAN ILMU PENDIDIKAN UNIVERSITAS RIAU - Rabbiah Al Adawiyah; Gimin Gimin; Zahirman Zahirman (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: This study aims to determine the comparative study of learning outcomes of students who work and do not work Pancasila and Civics Education Study Program Faculty of Teacher Training and Education University of Riau Respondents in this study were 65 people using Purposive Sampling techniques and different test. Data collection techniques carried out are through observation, questionnaires, interviews, and documentation. The research method used is qualitative descriptive analysis. This method is used to process the results of research in order to obtain a conclusion. Based on the results of research conducted on the comparative study of learning outcomes of students who work and do not work Pancasila and Civics Education Study Program Faculty of Teacher Training and Education, University of Riau, it can be concluded that there are differences in learning outcomes of students who work and do not work, namely the average value the average student working is 3.28 and students who don't work 3.41. Based on the results of research and data analysis, the researchers provide recommendations that are to students, especially those who work, should be able to focus on lecture activities because there are differences in learning outcomes that are lower than students who do not work. For the University, especially the teaching staff gives understanding to students to prioritize learning activities on campus so that learning outcomes can be maximized.Key Words: Learning Outcomes, Working